Bone description of the Andean puma (Puma concolor): I. Appendicular skeleton - Pacheco C., Joel (2017)
The appendicular skeleton of the Andean puma (Puma concolor) of two specimens (one male, one female) is described. Both animals were seized in Cusco, Peru by the National Forest and Wildlife Service (SERFOR). The bones were obtained following the standard technique of osteological dissection. The description of the anatomical terms was made according to the Veterinary Anatomical List. The most outstanding characteristics of the appendicular skeleton were described. In general, the eminences of the bones are not so conspicuous and only appear as rough areas. Complete radius and ulna with well-defined articular veneers. At the level of the hands the radial carpi stand out, the metacarpi slightly cylindrical and curved in the palmar surface, the third phalanx of the first finger is quite developed and with the prominent ungueal apophysis characteristic of these species. A well-defined spherical femoral head is present at the level of the two well-defined sesamoid gastrocnemius condyles; tibia and fibula are complete. In the tarsus, in number of seven, excel the astragalus and the calcaneus. The metatarsals and phalanges are very like those of the hand. At the level of the hip, the compact bones resemble those of the domestic cat.